Neurobehavioral effects of cyanobacterial biomass field extracts on zebrafish embryos and potential role of retinoids - Pípal, Marek; Legradi, Jessica; Smutná, Marie; Kočí, Tereza; Priebojová, Jana; Bláhová, Lucie; Krauss, Martin; Hilscherová, Klára (Aquatic toxicology (Amsterdam, Netherlands), 2020)
Cyanobacteria are known for their ability to produce and release mixtures of up to thousands of compounds into the environment. Recently, the production of novel metabolites, retinoids, was reported for some cyanobacterial species along with teratogenic effects of samples containing these compounds. Retinoids are natural endogenous substances derived from vitamin A that play a crucial role in early vertebrate development. Disruption of retinoid signalling- especially during the early development of the nervous system- might lead to major malfunctions and malformations. In this study, the toxicity of cyanobacterial biomass samples from the field containing retinoids was characterized by in vivo and in vitro bioassays with a focus on the potential hazards towards nervous system development and function. Additionally, in order to identify the compounds responsible for the observed in vitro and in vivo effects the complex cyanobacterial extracts were fractionated (C18 column, water-methanol gradient) and the twelve obtained fractions were tested in bioassays. In all bioassays, all-trans retinoic acid (ATRA) was tested along with the environmental samples as a positive control. Retinoid-like activity (mediated via the retinoic acid receptor, RAR) was measured in the transgenic cell line p19/A15. The in vitro assay showed retinoid-like activity by specific interaction with RAR for the biomass samples. Neurotoxic effects of selected samples were studied on zebrafish (Danio rerio) embryos using the light/dark transition test (Viewpoint, ZebraLab system) with 120 hpf larvae. In the behavioural assay, the cyanobacterial extracts caused significant hyperactivity in zebrafish at 120 hpf after acute exposure (3 h prior to the measurement) at concentrations below the teratogenicity LOEC (0.2 g dw L-1). Similar effect was observed after exposure to fractions of the extracts with detected retinoid-like activity and additive effect was observed after combining the fractions. However, the effect on behaviour was not observed after exposure to ATRA only. To provide additional insight into the behavioural effects and describe the underlying mechanism gene expression of selected biomarkers was measured. We evaluated an array of 28 genes related to general toxicity, neurodevelopment, retinoid and thyroid signalling. We detected several affected genes, most notably, the Cyp26 enzymes that control endogenous ATRA concentration, which documents an effect on retinoid signalling.
Keywords: biotest; dánio pruhované; Animals; Cyanobacteria; Retinoids; sinice; chemické látky znečišťující vodu; Cell Line, Tumor; Tretinoin; Biomarkers; Biomass; Water Pollutants, Chemical; embryo nesavčí; tretinoin; chování zvířat; Mice; myši; Locomotor response; Zebrafish; ATRA; Receptors, Retinoic Acid; Biological Assay; Gene Expression; Behavior, Animal; exprese genu; Embryo, Nonmammalian; zvířata; receptory kyseliny retinové; biomasa; nádorové buněčné linie